2023
DOI: 10.1002/hsr2.1600
|View full text |Cite
|
Sign up to set email alerts
|

Beyond scientific and technical training: Assessing the relevance of empathy and assertiveness in future physiotherapists: A cross‐sectional study

Juan‐Elicio Hernández‐Xumet,
Alfonso‐Miguel García‐Hernández,
Jerónimo‐Pedro Fernández‐González
et al.

Abstract: Background and AimsEmpathy and assertiveness are two essential social skills for a health professional such as a physiotherapist and are necessary for developing moral thinking. Previous studies show that the development of empathy and other social skills improves as students progress in their studies. However, other authors show deterioration of empathy as students progress in their studies and acquire clinical experience. Training in soft skills, such as assertiveness, among health science students will have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 61 publications
(181 reference statements)
0
0
0
Order By: Relevance
“…It is, therefore, clear that the higher the level of assertiveness, the higher the level of self-esteem 54 . This correlates with the study by Hernández-Xumet et al 1 , in which it was observed that, among physiotherapy students, those with low scores in assertiveness development were those with higher scores at the empathic level in the area of personal distress (PD), which includes the negative feelings, anxiety, unease and personal discomfort generated when empathising with others.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is, therefore, clear that the higher the level of assertiveness, the higher the level of self-esteem 54 . This correlates with the study by Hernández-Xumet et al 1 , in which it was observed that, among physiotherapy students, those with low scores in assertiveness development were those with higher scores at the empathic level in the area of personal distress (PD), which includes the negative feelings, anxiety, unease and personal discomfort generated when empathising with others.…”
Section: Introductionsupporting
confidence: 90%
“…Another possibility is that assertiveness is related to the ability to cope with stress and anxiety. In this case, assertive people are more likely to have healthy coping strategies, which may help them manage stress and anxiety more effectively, as has been reported in other studies mentioned above 1 , 53 , 54 .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations